To solve the inequality -y/2 < 3, we need to isolate y.
First, we'll multiply both sides of the inequality by -2 (remember when we multiply or divide by a negative number, we need to switch the inequality sign):
(-2)(-y/2) > 3(-2)
y > -6
The solution to the inequality is y > -6, which means that y can take any value greater than -6.
To graph this solution, we'll draw an open circle at -6 on the number line to indicate that -6 is not included in the solution, and then shade to the right since y can be any value greater than -6.
The graph would look like this:
<-------------(===============================================>
Choose the correct solution and graph for the inequality -y/2<3
1 answer